Concussion Symptom Profiles Among Child, Adolescent, and Young Adult Athletes. Issue 5 (September 2019) - Howell, David R.; Kriz, Peter; Mannix, Rebekah C.; Kirchberg, Tyler; Master, Christina L.; Meehan, William P.
Abstract : Objectives: (1) To examine how age influences initial symptom presentation following concussion; and (2) to determine whether specific symptom profiles are associated with duration of postconcussion symptoms, and whether they vary by age group. Design: A total of 689 patients (20% children 7-12 years of age, 69% adolescents 13-18 years of age, and 11% young adults 19-30 years of age) were seen and diagnosed with a concussion within 21 days after injury. Patients completed the Post-Concussion Symptom Scale (PCSS) and were followed until they no longer required care. Setting: Two specialty care sport concussion clinical practices. Main outcome measures: Overall PCSS score was obtained, as well as severity ratings from somatic, vestibular–ocular, cognitive, sleep, and emotional symptom domains. We also calculated total symptom duration time. Results: No significant main effect of age, or age by sex associations were identified among the symptom domains. Females endorsed a higher somatic symptom severity rating than males (9.8 ± 6.7 vs 8.1 ± 6.7; P = 0.03). For patients between 7 and 12 years of age, higher somatic [β-coefficient = 1.57, 95% confidence interval (CI), 1.47-1.67] and cognitive (β-coefficient = 2.50, 95% CI, 2.32-2.68) symptom severities were associated with longer duration of concussion symptoms. Among adolescents, longer total symptom duration was associated with more severe somatic (β-coefficient = 1.25, 95% CI, 0.34-2.15) and vestibular–ocular (β-coefficient = 2.36, 95% CI, 1.49-3.23) symptoms. Conclusions: Within 21 days after concussion, symptom-reporting behavior seems to be similar across the age spectrum, but the relationship between symptom profiles and time to symptom resolution varies by age. Although overall symptom ratings are beneficial in determining clinical pathways, symptom domain use may provide a beneficial method to determine individualized patient care that differs between children and adolescents after concussion.